Growth charts for children-Which ones to use in post Covid era? - Mrudula, Phadke; Sujata, Saunik; Rajlakshmi, Nair; Raju, Jotkar; Pramila, Menon (International Journal of Nutrition, 2023)
A practical review compares growth chart standards and references for pediatric monitoring after the COVID era. It advises on selection, interpretation, and equity considerations in diverse populations.